Code-Switching Used by Felicia Putri Tjiasaka and Timothy Ronald on YouTube Videos on Crypto Investment - Samuel Yosafat Wibisono (Institute of Research and Community Outreach - Petra Christian University, 2026)
This study examines code-switching patterns used by Indonesian finance influencers Felicia Putri Tjiasaka and Timothy Ronald in their YouTube videos on crypto investment. Drawing on Hoffmann's (1991) framework, it analyzes their bilingual linguistic repertoire through intra-sentential, inter-sentential, and emblematic switching. Qualitative analysis of transcribed videos revealed that intra-sentential switching dominates (92.47% for Felicia, 95.79% for Timothy). Felicia employs code-switching to foster engagement and relatability, blending Indonesian with English for audience closeness. Conversely, Timothy uses English technical terms to enhance clarity, accuracy, and professional credibility in financial explanations. While both heavily utilize code-switching, their strategies diverge: engagement versus expertise. These findings highlight code-switching as a strategic tool for personal branding and effective bilingual communication in digital crypto investment education on YouTube.